2015
DOI: 10.1088/1741-2560/12/6/066017
|View full text |Cite
|
Sign up to set email alerts
|

Neural dynamics during repetitive visual stimulation

Abstract: These findings have direct implications on the use of RVS and SSVEPs for neural process investigation through steady-state topography, controlled entrainment of brain oscillations and BCIs. A deep understanding of SSVEP propagation in time and space and the link with ongoing brain rhythms is crucial for optimizing the typical SSVEP applications for studying, assisting, or augmenting human cognitive and sensorimotor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
2
17
2
Order By: Relevance
“…Crevier and Meister reported subharmonic components for stimulus frequencies between 30-70 Hz [13]. Tsoneva et al have observed subharmonic generation in the 40-60 Hz stimulus frequency range [14]. In addition to these studies, in our previous work, our results showed subharmonic generation for the stimulus range of 15-42 Hz [15].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Crevier and Meister reported subharmonic components for stimulus frequencies between 30-70 Hz [13]. Tsoneva et al have observed subharmonic generation in the 40-60 Hz stimulus frequency range [14]. In addition to these studies, in our previous work, our results showed subharmonic generation for the stimulus range of 15-42 Hz [15].…”
Section: Introductionsupporting
confidence: 79%
“…Period doubling in SSVEP experiments have been consistently observed across different studies [2,6,[13][14][15]. The occurrence of period doubling has been speculated to be by 'entrainment' of intrinsic brain oscillations to half of the external stimulation frequency [14,16,17,29]. Tsoneva et al define the term entrainment as the synchronization of naturally ongoing oscillations to an external force [14].…”
Section: Discussionmentioning
confidence: 98%
“…They have used square wave light source with 2 Hz steps, excluding 50 Hz. They reported subharmonic responses throughout this stimulus frequency range along with valuable spatiotemporal information regarding SSVEPs [8].…”
Section: Introductionmentioning
confidence: 94%
“…SSVEPs have been widely used in engineering applications such as brain-computer interfaces (BCIs) [3] and cognitive and clinical research [4,5], however, there is not a precise explanation about their mechanism of generation. In particular, some nonlinear resonance phenomena of SSVEPs, which have been observed by several researchers [6][7][8][9], need to be better understood. These phenomena are characterized by brain responses at harmonic and subharmonic frequencies (period doubling (PD) behavior) as well as the response to the stimulus frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was reasonable due to the relations between the right-handed driven motor task and the increased excitability over the left primary motor cortex. The locally decreased IAB was probably associated with the excitability enhancement of motor cortex [12] while the increased IAB could be caused by the excitability inhibition of other regions, which resembled the 'focal ERD/surround ERS' phenomenon [13,14]. It was interesting that HIAB and LIAB showed opposite change in all channels and the locally decreased IAB might result from obviously the decrease of HIAB and the increase of LIAB in all brain regions.…”
Section: Discussionmentioning
confidence: 95%